Uncertainty in vibration energy flow analysis - BOCHNIAK, W.; CIEŚLIK, J. (Archives of Acoustics, 2005)
Introducing uncertainty considerations into simulation will facilitate exactitude assessment and help to boost the designer’s confidence in simulation. The sources of uncertainty marked as the sensitivity parameters have an impact on the vibrational energy flow simulation and must be factored into the solution process. One of these parameters, the excitation frequency, has been identified and analyzed. The techniques for quantifying the effects of uncertainties are presented. The transmission of vibrational energy flow in plates is analyzed by the structural intensity method. A typical case for vehicle structures has been selected as an example: a simply supported plate under tangential force excitation. The relations between the structural intensity distribution and structural mode shapes and the effects of excitation frequency on the changes of energy flow in plate are discussed. Finally, the potential application of the structural intensity technique towards for the design of vehicle structures is discussed.